The Effectiveness of Mindfulness Implementation on Academic Stress among First-Year University Students - Khoirotus Silfiyah Dara Nur Fadilla; Yanuari Srianturi (Ma'soem University, 2025)
This study examines the effectiveness of mindfulness implementation in reducing academic stress among first-year students of the Guidance and Counseling Study Program at UNUGIRI Bojonegoro. The study is motivated by the fact that first-year students are highly vulnerable to academic stress due to transitional demands, including adapting to a new learning system, increased academic workload, and higher achievement expectations. The purpose of this study is to determine the level of academic stress experienced by first-year students. This research employed a quantitative experimental approach using a quasi-experimental design with a one-group pretest–posttest model. The research subjects consisted of 30 first-year students. Academic stress was measured before and after the mindfulness intervention using a standardized stress scale. Data were analyzed using SPSS software, including normality testing and a paired-samples t-test. The normality test showed a p-value of 0.954, indicating that the data were normally distributed. The research hypothesis was that implementing mindfulness is effective in reducing academic stress among first-year students. The results showed that the mean pretest score before the mindfulness intervention was 95.37, while the mean posttest score after the intervention was 68.37. Descriptive analysis revealed a significant decrease in the mean academic stress scores from pretest to posttest. Statistical analysis indicated that the mindfulness intervention contributed positively to the management of academic stress among participants. These findings demonstrate that mindfulness implementation positively supports first-year Guidance and Counseling students at UNUGIRI Bojonegoro in managing academic stress. Through mindfulness practice, students are trained to become more aware of their thoughts, emotions, and experiences, to accept academic pressures without excessive reactions, and to develop a calmer and more adaptive perspective in responding to various academic demands.